Evaluation of Resistance to Root-knot Nematode (Meloidogyne graminicola) in Asian Rice Varieties and the Associated Biochemical Changes Induced due to Nematode Infestation (Indian Journal of Nematology, 2024)
Rice root-knot nematode, Meloidogyne graminicola is one of the significant constraints in India’s primary rice-growing regions. In the current study, the reaction of Asian rice varieties released by ICAR-NRRI was assessed against rice root-knot nematode, M. graminicola under artificial inoculation conditions. Among the 110 varieties screened against M. graminicola, 14  were reported to be highly susceptible, 64 were recorded as susceptible, and 32 registered moderately resistant reactions. In susceptible and highly susceptible varieties, the conversion per cent of juveniles to females was higher than in moderately resistant varieties. Highest defense enzyme activities (catalase and superoxide dismutase) and chlorophyll content were recorded in moderately resistant variety, which suggests the role of defense enzymes in conferring resistance to the rice plants.